The Moderating Effect of Earnings Persistence on the Relationship Between International Financial Reporting Standards Implementation and Earnings Response Coefficient of Listed Companies in Nigeria - Sunny Biobele Beredugo (Journal of Accounting and Taxation, 2023)
This study examined the moderating effect of earnings persistence on the relationship between International Financial Reporting Standards (IFRS) Implementation and Earnings Response Coefficient (ERC) of listed companies in Nigeria. This was done to evaluate the reason behind the poor utilization of capital market, especially equity market for funding of developmental project by both public and private sector entities. This study adopted historical-descriptive and content analysis research designs. This was conducted using forty six listed companies in Nigerian covering the period of 6 years (2013 to 2018). The data of the study was analyzed using the Partial Least Square. The results of the cross sectional effect model show that IFRS implementation brings about high quality information, but it is not sufficient enough to induce a change in the ERC. It was discovered that investors and speculators alike pay close attention to the degree to which current period earnings shocks persist in the future, and this outcome propels the IFRS compliance to enhance a high earnings response coefficient of firms in the stock market. It is therefore recommended that the financial reports of listed companies in Nigerian should be designed to improve the information contents of accounting earnings in order to include inherent socio-economic risk, full disclosure of net income, past and prospective earnings